1992
DOI: 10.1007/bf00638235
|View full text |Cite
|
Sign up to set email alerts
|

Role of prostanoids in the inflammatory reaction and their therapeutic potential in the skin

Abstract: Vasodilatory prostaglandins (PG), contributing to the inflammatory reaction, have gained considerable attention. It is becoming apparent that PG have pharmacological effects traceable to biological activities distinct from smooth muscle relaxation. The data from pharmacological experiments presented here indicate the diverse action of vasodilatory PG analogues in the skin of laboratory animals. Nocloprost, a stable PGE2 analogue, induced erythema in intact skin of rats when applied topically and inhibited in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…We observed that MPO activity (used as an indirect measure of PMN infiltration) was significantly increased at 24 h after the challenge with OXA. This finding confirmed those made in various other models of dermal inflammation, in which the maximal neutrophilic infiltrate occurs at the same time point [ 38 – 40 ]. Although, in our model, the MPO activity at 48 h remained comparably high and did not decrease again until 72 h after the induction of the inflammation, the influence of 15-epi-LXA 4 on the PMN infiltration and likewise on the biosynthesis of pro- as well as anti-inflammatory and pro-resolving lipid mediators was examined after 24 h. We cannot compare the concentrations of prostaglandins, LTB 4 or various HETE with the inflammatory infiltrate, since these mediators were not analysed in previous publications dealing with dermal inflammation.…”
Section: Discussionsupporting
confidence: 91%
“…We observed that MPO activity (used as an indirect measure of PMN infiltration) was significantly increased at 24 h after the challenge with OXA. This finding confirmed those made in various other models of dermal inflammation, in which the maximal neutrophilic infiltrate occurs at the same time point [ 38 – 40 ]. Although, in our model, the MPO activity at 48 h remained comparably high and did not decrease again until 72 h after the induction of the inflammation, the influence of 15-epi-LXA 4 on the PMN infiltration and likewise on the biosynthesis of pro- as well as anti-inflammatory and pro-resolving lipid mediators was examined after 24 h. We cannot compare the concentrations of prostaglandins, LTB 4 or various HETE with the inflammatory infiltrate, since these mediators were not analysed in previous publications dealing with dermal inflammation.…”
Section: Discussionsupporting
confidence: 91%
“…16-phenoxy-LXA 4 , which resists enzymatic degradation and is a potent inhibitor of neutrophil adhesion and transmigration in vitro (24), applied topically to mouse ear skin just prior to induction of inflammation, clearly blocks neutrophil infiltration in a concentration-dependent fashion. Thus the inhibitory actions of LX and 15-epi-LXA 4 stable analogs reviewed here provide additional evidence for the ability of LX and aspirin-triggered LX to block neutrophil migration, which appears to be a unique action of lipoxins when compared to other lipid mediators or eicosanoids that either initiate (i.e., LTB 4 ) or enhance (PGE 2 , PGI 2 ) this response in vivo (7,38). It is of particular interest to point out that other eicosanoid stable analogs such as the analog of PGI 2 , Iloprost, significantly enhance LTB 4 -induced leukocyte infiltration in this mouse ear model (38), as did PGE 2 (see Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Yet another means of inducing leukocyte influx is the application of compounds with intrinsic pro‐inflammatory capacities (Table 2). Substances frequently used for this purpose comprise the stable prostaglandin analogue Iloprost (131) and the calcium ionophore A‐23187 (132). The former enhances leukotriene B 4 ‐induced inflammation, whereas the calcium ionophore‐induced inflammation is mediated by endogenous leukotriene B 4 .…”
Section: Intravital Microscopymentioning
confidence: 99%